Pengembangan Media Magic Geometry pada Materi Bangun Ruang Kelas IV Sekolah Dasar - Mukti Sintawati; Mifta Rudiyanta; Muhammad Nuryanto (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
Learning mathematics in elementary school is expected to adjust to the cognitive development of students. Abstract mathematical concepts make students need help to understand them. This study aims to develop mathematics learning media geometry for 4th grade elementary school students. This development research uses the Borg & Gall research model which was carried out to the seventh stage, namely research and information collecting, planning, developing preliminary form a product, preliminary field testing, main product revision, main field testing, and operational product revision. Product trials were conducted at Ngablak Public Elementary School. Data collection instruments were using a questionnaire. The questionnaire used to assess the appropriateness of the media was an expert validation assessment sheet, while the teachers’ assessment sheet and students’ response questionnaire were used to determine the practicality of the product. The validation results from the experts obtained that the Magic Geometry media was declared very appropriate to be used in learning mathematics with an average score of 4.45. The results of the teacher practicality assessment were stated to be very practical with a score of 4.9 and the student’s response questionnaire received an average score of 4.2 with a practical category. The results of the student response questionnaire also showed that Magic Geometry made learning becomes more interesting and materials easier to understand.